Keras in motion - Boxel, Dan Van (Manning, 2017)
"Keras in Motion teaches you to build neural-network models for real-world data problems using Python and Keras. In over two hours of hands-on, practical video lessons, you'll apply Keras to common machine learning scenarios, ranging from regression and classification to implementing Autoencoders and applying transfer learning. In each crystal-clear video module, you'll put your new knowledge into practice, as you teach your network to recognize text and even create an algorithm for a self-driving car!"--Resource description page